Physics studies and generic attributes - Phang, Fatin Aliah (2012)
The purpose of this study is to investigate and understand the perception of physics undergraduates, lecturers and employers on the learning of UniversitiTeknologi Malaysia (UTM) graduate's generic attributes through physics studies. A total of 104 physics undergraduates and 27 physics lecturers participated in the questionnaire survey while three employers participated in semi-structured interview. Mann-Whitney U test and Wilcoxon Signed Ranks test with significant level of p = 0.05 were used to evaluate the data collected from the questionnaires. Interview data were recorded and summarized to identify key categories and features. The results indicated a development gap among undergraduates, lecturers and employers.